2007
DOI: 10.1227/01.neu.0000279972.95060.cb
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Neuropsychological Function and Post-Concussion Symptoms of Concussed Collegiate Athletes

Abstract: OBJECTIVE:Our purpose was to determine whether sex differences exist with respect to post-concussion symptoms and neurocognitive function in concussed collegiate athletes. METHODS: A prospective dependent-sample cohort design was used to compare baseline and post-concussion neuropsychological test scores and endorsed symptoms as functions of serial post-concussion assessment with respect to time and sex. The Immediate Post-concussion Assessment and Cognitive Testing (ImPACT) battery was administered to a multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
204
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 265 publications
(223 citation statements)
references
References 30 publications
13
204
6
Order By: Relevance
“…Consistent with epidemiological findings, postinjury symptomology differed between males and females 12, 64. Males given mTBIs exhibited greater impairment on the cognitive task (i.e., NCM), whereas females given mTBIs exhibited increased impairments on the forced swim task.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Consistent with epidemiological findings, postinjury symptomology differed between males and females 12, 64. Males given mTBIs exhibited greater impairment on the cognitive task (i.e., NCM), whereas females given mTBIs exhibited increased impairments on the forced swim task.…”
Section: Discussionsupporting
confidence: 75%
“…As males and females often report different PCS symptoms,11, 12 understanding whether or not underlying structural or epigenetic changes following mTBI and RmTBI contribute to these heterogeneous outcomes is an important undertaking. Owing to sex differences in brain maturation,7 an injury at a given age has the potential to affect the developmental trajectory of males and females in distinct ways.…”
Section: Introductionmentioning
confidence: 99%
“…However, most investigators have studied collegiate athletes, and whether high school athletes will behave similarly is uncertain. Covassin et al 21 reported differences in visual memory composite scores in collegiate athletes and suggested a relationship between postconcussive symptoms and sex. In a mixed sample of collegiate and high school athletes, Broshek et al 22 found that females tended to be more cognitively impaired after a sport-related concussion.…”
mentioning
confidence: 99%
“…Indeed, studies have reported a higher incidence of concussions in females (Castile, Collins, McIlvain, & Comstock, 2012;Gessel, SK, Collins, Dick, & RD, 2007). Further, it has also been suggested that women may take longer to recover from a concussion than men (Colvin et al, 2009;Covassin, Schatz, & Swanik, 2007).…”
Section: Influence Of Gender On Continuing To Play And/or Not Reportmentioning
confidence: 99%
“…However, we hypothesized attitudes between males and females would differ. Based on the literature about gender to date, and the studies that showed a difference (for example Colvin et al, 2009;Covassin et al, 2007;Covassin et al, 2012a), we hypothesized that males would report that they would continue to play with a concussion, admire elite athletes who played on after a concussion, but would be less likely to complete rehabilitation. Further, we also hypothesized differences based upon previous concussion.…”
Section: Aim Of the Studymentioning
confidence: 99%